MODERN APPROACHES OF TEACHING WRITING IN ENGLISH LANGUAGE (Лучшие интеллектуальные исследования, 2024)
Abstract: The article is devoted to the formation of a foreign language communicative  students' competencies in the field of writing. The author gives definitions of writing speech, introduces two approaches to teaching writing, names  the stages teaching creative writing, criteria for evaluating written messages, talks about communicative writing assignments.